A Comparative Study to Assess the Impact Of 6 Days Core Competency Training of The ANMs of Damoh District Of Madhya Pradesh - Prasad, Pankaj; Singh Arya, Rajendra; Bansal, Manoj; Singh, S P (National Journal of Community Medicine, 2012)
Background: In India, public health nursing in the villages today is still limited to services rendered by Auxiliary Nurse Midwife (ANM). ANMs are regarded as the first contact person between people and organization, between needs and services and between consumer and provider. Recognizing this fact Japanese International Cooperation Agency (JICA) gave 6 days Core Competency Training to ANMs of Damoh district about Ante-Natal Care (ANC) check-up. Objective: To confirm the impact of the 6 days Core Competency training of the ANMs. Materials & Methods: The present study was a Case Control Study which was carried out in JICA/MP, RHP (Japan International Cooperation Agency/ Madhya Pradesh – Reproductive Health Project) intervened district i.e. Damoh and one of Non-Project district i.e. Sagar during January and February 2011. In total 30 ANMs were interviewed each from Damoh and Sagar district. Firstly, 3 blocks were randomly selected each from 7 blocks of Damoh and 11 blocks of Sagar respectively and than 10 ANMs were again randomly selected from each block. Statistical analysis: Percentage, proportions and appropriate Test of Significance (Fisher’s Exact Test) were applied to interpret the result. Results: All the ANMs (100%) in Damoh district enumerated PROM (Pre-Mature Rupture of Membrane) as complication during Pregnancy as against 76.67% in Sagar district. 60% of ANMs in Damoh district appreciated Fetal Heart Sound (FHS) correctly as compared to merely 16.67% in Sagar district. Conclusion: The findings in present study clearly show that such kind training which emphasize on improving the practical knowledge and skills of ANMs should be provided on regular basis. Impact of such training can be enhanced in the field if timely refresher or reorientation trainings are given to those who have been already trained.